Mobile gaming sudoku - Lu, Meng. (2011)
The Sudoku is one of the most popular puzzle games that appear in hundreds of newspapers every day. Nowadays, it has gone beyond the papers and being implemented as a software game for several devices. It requires some little brainwork to give a feeling of satisfaction, without taking up huge amounts of time.